Low-noise, low-offset modulator demodulator circuit for chopper stabilization technique in CMOS-MEMS sensor applications - Sutri, N.Y. (IEEE Computer Society, 2014)
This paper presents a design and technique for low noise, low offset modulation demodulation circuit for chopper stabilized amplifiers use in CMOS-MEMS sensor applications. In these sensors, where the sensed signals are usually very weak, a low-noise interface readout circuit plays a crucial role in determining the overall sensor performance and success in the market. Amplifiers are the core building blocks of these circuits and hence there is a growing demand for low noise and low offset designs and fabrication. Chopper stabilization technique has been widely used in amplifiers for flicker (1/f) noise and offsets reduction purposes using the principles of modulation and demodulation. Thus, the functionality and performance of the modulation and demodulation circuit determines the realization and attainment of chopper stabilization. The demonstrated circuits in this work are designed in MIMOS 0.35 Î¼m AMS CMOS 3.3 V CMOS process technology. Cadence Spectre simulation results show the presented circuit achieves chopper stabilization with total noise contribution of 0.885 nVâHz and minimized offset. Â© 2014 IEEE.